Additively Manufactured Multiphasic Bone–Ligament–Bone Scaffold for Scapholunate Interosseous Ligament Reconstruction. Issue 14 (21st May 2019) - Lui, Hayman; Bindra, Randy; Baldwin, Jeremy; Ivanovski, Saso; Vaquette, Cedryck
Abstract: The scapholunate interosseous ligament (SLIL) is a frequently torn wrist ligament, and current surgical options for SLIL tears are suboptimal. This research aims to develop a novel multiphasic bone–ligament–bone scaffold (BLB) with a porous interface using 3D‐printing and cell sheet technology for the reconstruction of the dorsal scapholunate interosseous ligament. The BLB comprises two bone compartments bridged by aligned polycaprolactone fibers mimicking the architecture of the native tissue. Mechanical testing of the BLBs shows their ability to withstand physiological forces. Combination of the BLB with human bone marrow mesenchymal stem cell sheet demonstrates that the harvesting did not compromise cell viability, while allowing homogeneous distribution in the ligament compartment. The BLBs are loaded with cell sheets and bone morphogenetic protein‐2 in the ligament and bone compartment respectively prior to ectopic implantation into athymic rats. The histology demonstrates rapid tissue infiltration, high vascularization, and more importantly the maintenance of the compartmentalization as bone formation remains localized to the bone compartment despite the porous interface. The cells in the ligament compartment become preferentially aligned, and this proof‐of‐concept study demonstrates that the BLB can provide sufficient compartmentalization and fiber guiding properties necessary for the regeneration of the dorsal SLIL. Abstract : A bone–ligament–bone scaffold is fabricated via continuous additive manufacturing for regeneration of the scapholunate interosseous ligament. The scaffold comprises two bone compartments bridged by aligned fibers mimicking the architecture of the native tissue. Subcutaneous implantation in rats demonstrates maintenance of compartmentalization upon injection of an osteogenic cue in the bone compartment and cell sheets in the ligament compartment.